Endoscopic diagnosis and management of esophagogastric variceal hemorrhage: European Society of Gastrointestinal Endoscopy (ESGE) Guideline - Gralnek, Ian M.; Camus Duboc, Marine; Garcia-Pagan, Juan Carlos; Fuccio, Lorenzo; Karstensen, John Gásdal; Hucl, Tomas; Jovanovic, Ivan; Awadie, Halim; Hernandez-Gea, Virginia; Tantau, Marcel; Ebigbo, Alanna; Ibrahim, Mostafa; Vlachogiannakos, Jiannis; Burgmans, Marc C.; Rosasco, Robyn; Triantafyllou, Konstantinos (Endoscopy, 2022)
1 ESGE recommends that patients with compensated advanced chronic liver disease (ACLD; due to viruses, alcohol, and/or nonobese [BMI < 30 kg/m2] nonalcoholic steatohepatitis) and clinically significant portal hypertension (hepatic venous pressure gradient [HVPG] > 10 mmHg and/or liver stiffness by transient elastography > 25 kPa) should receive, if no contraindications, nonselective beta blocker (NSBB) therapy (preferably carvedilol) to prevent the development of variceal bleeding.Strong recommendation, moderate quality evidence.2 ESGE recommends that in those patients unable to receive NSBB therapy with a screening upper gastrointestinal (GI) endoscopy that demonstrates high risk esophageal varices, endoscopic band ligation (EBL) is the endoscopic prophylactic treatment of choice. EBL should be repeated every 2–4 weeks until variceal eradication is achieved. Thereafter, surveillance EGD should be performed every 3–6 months in the first year following eradication.Strong recommendation, moderate quality evidence.3 ESGE recommends, in hemodynamically stable patients with acute upper GI hemorrhage (UGIH) and no history of cardiovascular disease, a restrictive red blood cell (RBC) transfusion strategy, with a hemoglobin threshold of ≤ 70 g/L prompting RBC transfusion. A post-transfusion target hemoglobin of 70–90 g/L is desired.Strong recommendation, moderate quality evidence.4 ESGE recommends that patients with ACLD presenting with suspected acute variceal bleeding be risk stratified according to the Child–Pugh score and MELD score, and by documentation of active/inactive bleeding at the time of upper GI endoscopy.Strong recommendation, high quality of evidence.5 ESGE recommends the vasoactive agents terlipressin, octreotide, or somatostatin be initiated at the time of presentation in patients with suspected acute variceal bleeding and be continued for a duration of up to 5 days.Strong recommendation, high quality evidence.6 ESGE recommends antibiotic prophylaxis using ceftriaxone 1 g/day for up to 7 days for all patients with ACLD presenting with acute variceal hemorrhage, or in accordance with local antibiotic resistance and patient allergies.Strong recommendation, high quality evidence.7 ESGE recommends, in the absence of contraindications, intravenous erythromycin 250 mg be given 30–120 minutes prior to upper GI endoscopy in patients with suspected acute variceal hemorrhage.Strong recommendation, high quality evidence.8 ESGE recommends that, in patients with suspected variceal hemorrhage, endoscopic evaluation should take place within 12 hours from the time of patient presentation provided the patient has been hemodynamically resuscitated.Strong recommendation, moderate quality evidence.9 ESGE recommends EBL for the treatment of acute esophageal variceal hemorrhage (EVH).Strong recommendation, high quality evidence.10 ESGE recommends that, in patients at high risk for recurrent esophageal variceal bleeding following successful endoscopic hemostasis (Child–Pugh C  ≤ 13 or Child–Pugh B > 7 with active EVH at the time of endoscopy despite vasoactive agents, or HVPG > 20 mmHg), pre-emptive transjugular intrahepatic portosystemic shunt (TIPS) within 72 hours (preferably within 24 hours) must be considered.Strong recommendation, high quality evidence.11 ESGE recommends that, for persistent esophageal variceal bleeding despite vasoactive pharmacological and endoscopic hemostasis therapy, urgent rescue TIPS should be considered (where available).Strong recommendation, moderate quality evidence.12 ESGE recommends endoscopic cyanoacrylate injection for acute gastric (cardiofundal) variceal (GOV2, IGV1) hemorrhage.Strong recommendation, high quality evidence.13 ESGE recommends endoscopic cyanoacrylate injection or EBL in patients with GOV1-specific bleeding.Strong recommendations, moderate quality evidence.14 ESGE suggests urgent rescue TIPS or balloon-occluded retrograde transvenous obliteration (BRTO) for gastric variceal bleeding when there is a failure of endoscopic hemostasis or early recurrent bleeding.Weak recommendation, low quality evidence.15 ESGE recommends that patients who have undergone EBL for acute EVH should be scheduled for follow-up EBLs at 1- to 4-weekly intervals to eradicate esophageal varices (secondary prophylaxis).Strong recommendation, moderate quality evidence.16 ESGE recommends the use of NSBBs (propranolol or carvedilol) in combination with endoscopic therapy for secondary prophylaxis in EVH in patients with ACLD.Strong recommendation, high quality evidence.